Miners leaders, 1926 (1926)
1926 1918-1939 "Miners leaders, 1926" [T0612.jpg], 1926 Miners' Federation of Great Britain representatives during the General Strike: l-r in foreground - Herbert Smith (President), T. Richards, W. P Richardson and A. J. Cook (Secretary)